Changing the narrative for hearing health in the broader context of healthy living: a call to action. (22nd July 2021) - Saunders, Gabrielle H.; Vercammen, Charlotte; Timmer, Barbra H. B.; Singh, Gurjit; Pelosi, Angela; Meis, Marcus; Launer, Stefan; Kramer, Sophia E.; Gagné, Jean-Pierre; Bott, Anthea
Abstract: Objective: To discuss the steps necessary to facilitate hearing health care in the context of well-being and healthy living Design: Common themes among the articles in this special supplement of the International Journal of Audiology were used to identify issues that must be addressed if audiology is to move from being hearing-focussed to taking a holistic perspective of hearing care in the context of healthy aging. These are discussed within the context of other published literature. Results and conclusions: Three needs were identified: (i) Increased interdisciplinary education to raise awareness of the interplay between hearing and health. (ii) Increased emphasis on counselling education in audiology programs so that audiologists are equipped with the knowledge, competence and confidence to provide counselling and emotional support to their patients, beyond care. (iii) Redefinition of therapeutic goal setting and hearing outcomes to include aspects of well-being, so that audiologists can capture and patients realise that that good hearing outcomes can have a direct positive impact on a person's quality of life that extends beyond their improved ability to hear. It was emphasised that each of these needs to be considered within the context of the audiologists' scope of practice and audiologists' well-being.